2019
DOI: 10.37194/jpmb.v1i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Value Added Intellectual Capital (VAIC) Sebagai Prediktor Nilai dan Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan di Sektor Miscellaneous, Consumer Goods Property, Real Estate & Building Construction dan Infrastructure, Utilities

Abstract: Penelitian ini dilatarbelakangi oleh perkembangan ilmu penge-tahuan dan teknologi yang menyebabkan banyaknya perusahaan membuat strategi bisnis berbasis ilmu pengetahuan yaitu intellec-tual capital (IC). Salah satu pengukuran yang dapat digunakan untuk mengukur IC adalah VAICTM yang dikembangkan oleh Pulic (2000). Tujuan dari penelitian ini adalah untuk menganalisa pengaruh antara intellectual capital terhadap nilai dan kinerja keuangan perusahaan. Metode penelitian yang digunakan adalah metode regresi linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…In contrast, research and development is a way for companies to gain a competitive advantage by innovating products to increase company productivity (Padgett & Galan, 2010). The results of this study are in line with the results of research which found that intellectual capital did not affect firm value (Adnan & Sudiman, 2019;Siregar & Safitri, 2019). The study results show that sustainability reporting has no positive and significant effect on firm value.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, research and development is a way for companies to gain a competitive advantage by innovating products to increase company productivity (Padgett & Galan, 2010). The results of this study are in line with the results of research which found that intellectual capital did not affect firm value (Adnan & Sudiman, 2019;Siregar & Safitri, 2019). The study results show that sustainability reporting has no positive and significant effect on firm value.…”
Section: Discussionsupporting
confidence: 87%
“…In one component of intellectual capital, namely innovation capital efficiency, not all companies budget for research and development costs in carrying out their company activities. The results of a survey conducted by the World Bank on 1,320 companies in Indonesia in 2015 showed that only 1.9% of Indonesian companies spent funds on research and development (Adnan & Sudiman, 2019;Agustia et al, 2020). In contrast, research and development is a way for companies to gain a competitive advantage by innovating products to increase company productivity (Padgett & Galan, 2010).…”
Section: Discussionmentioning
confidence: 99%